Golgi-electron microscopic study of sprouting endothelial cells in the neonatal rat cerebellar cortex - Nousek-Goebl, N A; Press, M F (Brain research, 1986)
Intraparenchymal postnatal development of the CNS vasculature proceeds by a process of vascular 'budding' or 'sprouting' from existing endothelial cells and elongation of these immature vessels. A modified Golgi technique combined with gold toning and deimpregnation was used to identify and characterize sprouting endothelial cells in the neonatal rat cerebellar cortex with light and electron microscopy. Sprouting endothelial cells were the terminal endothelial cells of immature, developing blood vessels and they had characteristic morphologic features. The most distinctive feature was an array of tentacular processes (0.1-0.2 micron in diameter and ca. 20 microns in length) which radiated from the apex of these cells in the presumed direction of vessel growth. Cytoskeletal microtubules and microfilaments were the characteristic organelles of these tentacles. Sprouting endothelial cells were thin (1-3 microns in diameter). lacked a vessel lumen and basement membrane, had abundant cytoplasmic organelles and a prominent nucleus and were closely associated with the subterminal endothelial cell without interendothelial gaps. The developing blood vessels had a blood-brain barrier which excluded intravenously injected colloidal carbon from the neuropil.